Comparing the original and biosimilar biotherapeutics of the monoclonal antibody eculizumab by intact mass measurement and middle-up mass spectrometry analysis - M. B. Degterev; R. R. Shukurov (Тонкие химические технологии)
Objectives. In this biosimilar research, we compare the monoclonal antibody eculizumab obtained from different drugs [original Soliris® (Alexion Pharmaceuticals) and candidate Elizaria® (Generium)] by intact mass measurement and middle-up mass spectrometry analysis to enhance the role of mass spectrometry methods in biopharmaceutical development processes.Methods. The intact mass measurement is performed using a high-resolution ESI-MS. The middle-up analysis is performed by reversed-phase high-performance liquid chromatography with ESI-MS detection, subsequent IdeS treatment of antibodies, and disulfide bond reduction.Results. We have shown some small differences between the original and candidate drugs in the minor glycans level. Man5 glycan is only found in the original Soliris, and G0 is only found in the Elizaria. Glycation sites are also found in the light chain and Fd subunits of the original Soliris. The glycation level does not exceed 4.4%. The non-clipped C-end lysine level and G0F glycan levels are slightly lower in the original Soliris. All registered differences are not crucial for eculizumab’s quality and do not affect its effectiveness and preclinical safety. Generally, the results show a high level of similarity between the original and candidate drugs.Conclusions. The comparative mass spectrometry analysis of eculizumab in the original Soliris and Elizaria allows us to estimate their high degree of similarity by molecular masses and major modification profiles.